2022
DOI: 10.1002/nau.24866
|View full text |Cite
|
Sign up to set email alerts
|

Incontinence and sleep disturbances in young children: A population‐based study

Abstract: Aims: Nocturnal enuresis (NE), daytime urinary incontinence (DUI), fecal incontinence (FI), as well as sleep and behavioral problems are common in young children. The aim of this study was to analyze the association of sleep and psychological parameters for all types of incontinence in a representative sample of young children. Methods: Six hundred thirty eight (of 1161) children with a mean age of 5.9 years (50.9% boys) were assessed during their mandatory school entry examination. The participation rate was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
(94 reference statements)
2
2
2
Order By: Relevance
“…Some of these studies did not exclude children with daytime wetting [5,6], and some used objective measures of sleep disturbances [5,8] which might explain the differences in ndings. In contrast to the study by von Gontard and colleagues [10], we found evidence that sleep problems (e.g., night-time waking, di culty going to sleep, getting up after being put to bed) were prospectively associated with incontinence, speci cally UI classes that were characterized by daytime wetting alone, or a combination of daytime and night-time wetting at school-age.…”
Section: Comparison With Previous Ndingscontrasting
confidence: 99%
See 4 more Smart Citations
“…Some of these studies did not exclude children with daytime wetting [5,6], and some used objective measures of sleep disturbances [5,8] which might explain the differences in ndings. In contrast to the study by von Gontard and colleagues [10], we found evidence that sleep problems (e.g., night-time waking, di culty going to sleep, getting up after being put to bed) were prospectively associated with incontinence, speci cally UI classes that were characterized by daytime wetting alone, or a combination of daytime and night-time wetting at school-age.…”
Section: Comparison With Previous Ndingscontrasting
confidence: 99%
“…The study found that sleep problems were not more common in children with bedwetting and/or daytime wetting compared with continent children. Contrary to earlier research, a notable nding of the study is that children with enuresis had fewer night-time awakenings than their peers who had attained night-time bladder control [10].…”
Section: Introductioncontrasting
confidence: 96%
See 3 more Smart Citations